IMPLEMENTASI STRATEGI DISCOVERY PADA PEMBELAJARAN TEMATIK TERPADU MATERI POKOK IPA SIFAT-SIFAT CAHAYA DI KELAS IV MI MA’ARIF GONDOSULI MUNTILAN TAHUN AJARAN 2018/2019 - Lailatul Munawwaroh (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2018)
This study aims to analyze the implementation of discovery strategies inintegrated thematic learning of IPA subject matter of light traits in fourth gradeMI Ma'arif Gondosuli Muntilan academic year 2018/2019. This study alsoexplains the effectiveness of discovery strategies in integrated thematic learningof IPA subject matter of light traits in the fourth grade of MI Ma'arif GondosuliMuntilan academic year 2018/2019. Research uses qualitative research usingobservation techniques, collection of data from the field, and documentation. Theresults of the study are as follows: First, the discovery strategy begins with a littleexplanation of the material then continues the students to do experiments whichinclude the nature of light can propagate particles, can penetrate clear objects,light can be reflected and can be refracted. This activity begins with studentsobserving the experiment, then asking, gathering information, reasoning andcommunicating orally and in writing in the form of reports. Second, theeffectiveness of this strategy is known from the enthusiasm of students in doinggroup work, dividing the tools that will be taken when conducting the experiment.In addition, this strategy can improve the creativity of students and teachers inconducting learning in order to foster a sense of enthusiasm in learning. Then incognitive values, after the post-test shows the value that exceeds the KKM exceptfor two students, where this can be an indicator of the effectiveness of the strategy.